Temporal reorganization to overcome monocular demyelination - Raz, Noa; Chokron, Sylvie; Ben-Hur, Tamir; Levin, Netta (Neurology, 2013)
To identify the source of delayed visual evoked potential (VEP) latencies in the fellow eyes of patients with optic neuritis (ON) and determine whether these latencies stem from clinically silent demyelination or reflect an adaptive process for synchronization with the affected eyes. The study sample comprised 17 patients whom we followed for 12 to 26 months after unilateral first-ever ON diagnosis and 17 age-matched controls. To avoid confounding effects of axonal loss, only intact fellow eyes (except for VEPs) were included. Subjects underwent standard visual evaluation, motion perception, as well as static and time-constrained stereo tasks. Assessments included VEP, optical coherence tomography, high-resolution MRI, and diffusion tensor imaging. We observed delayed VEP peaks (P100) in both affected and fellow eyes. However, while these were derived from prolonged time-to-start in the affected eyes, supporting the existence of demyelination, time-to-start in the fellow eyes was intact. VEP latencies in the fellow eyes could not be explained by demyelinative lesions along postchiasmal pathways (assessed by diffusion tensor imaging). Delayed peaks in fellow eyes resulted from a wider waveform, which evolved over time and occurred with a concomitant decrease in the gap in time between VEP peaks of both eyes. These changes offered a functional advantage; synchronization of inputs highly correlated with improved time-constrained binocular perception. Delayed latencies in the fellow eyes may reflect adaptive mechanisms at the cortical level that improve binocular integration over time to adjust for the damage incurred. These data provide a unique demonstration of temporal reorganization that compensates for delayed transmittal of visual information to the cortex.